Effect of Whole-body Vibration frequency on muscle tensile state during graded plantar flexor isometric contractions - Pornpimol Muanjai; Chris Haas; Wolfram Sies; Uwe Mittag; Jochen Zange; Eckhard Schönau; Ibrahim Duran; Sigitas Kamandulis; Jörn Rittweger (Elsevier, 2023)
Background: Acute physiological and biomechanical alterations have been reported following whole-body vibration (WBV). Stiffening of muscles has only been anecdotally reported in response to WBV. Accordingly, this study investigated active plantar flexor muscle stiffness in response to a single WBV bout at four mechanical vibration frequencies. Methods: Thirteen healthy adults (37.1 ± 14.4 years old) randomly received WBV in 4 different frequencies (6, 12, 24, and 0 Hz control) for 5 min. Shear wave speed (SWS) in longitudinal and transverse projections, architecture, and electric muscle activity were recorded in the medial gastrocnemius (MG) and soleus (SOL) muscle during graded plantar flexor contraction. Subjective rating of perceived muscle stiffness was assessed via Likert-scale. Results: SWS of the MG at rest was enhanced in response to 5 min of 24 Hz WBV (p = 0.025), while a small reduction in SOL SWS was found during contraction (p = 0.005) in the longitudinal view. Subjective stiffness rating was increased following 12 Hz intervention. After 24 Hz WBV, pennation angle for MG was decreased (p = 0.011) during contraction. As a secondary finding, plantar flexor strength was significantly increased with each visit, which, however, did not affect the study's main outcome because of balanced sequence allocation. Conclusion: SWS effects were solely limited to 24 Hz mechanical vibration and in the longitudinal projection. The observed effects are compatible with an interpretation by post-activation potentiation, warm-up, and force-distribution within the triceps surae muscles following 5 min WBV. The outcome may suggest SWS as a useful tool for assessing acute changes in muscle stiffness.